2022
DOI: 10.3389/fgene.2022.832809
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chloroplast Genomes Provides Insights Into the Evolution of Agropyron

Abstract: Plants of the Agropyron genus are important pasture resources, and they also play important roles in the ecological restoration. Chloroplast genomes are inherited from maternal parents, and they are important for studying species taxonomy and evolution. In this study, we sequenced the complete chloroplast genomes of five typical species of the Agropyron genus (eg., A. cristatum × A. desertorum Fisch. Schult, A. desertorum, A. desertorum Fisch. Schult. cv. Nordan, A. michnoi Roshev, and A. mongolicum Keng) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
4
5
0
Order By: Relevance
“…All Leymus species showed minor variations in junction positions of JLB (~13 bp), JSB (~34 bp), and JLA (~8 bp) ( Figure 7 ). In addition, ndhH was found to straddle the JSA, which is consistent with previous data on other Triticeae species, such as Agropyron , Hordeum , and Festuca [ 23 , 47 , 58 , 59 ]. The different position of ndhH in the JSA border suggests that these variations may be caused by intramolecular recombination during early evolution [ 60 , 61 , 62 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…All Leymus species showed minor variations in junction positions of JLB (~13 bp), JSB (~34 bp), and JLA (~8 bp) ( Figure 7 ). In addition, ndhH was found to straddle the JSA, which is consistent with previous data on other Triticeae species, such as Agropyron , Hordeum , and Festuca [ 23 , 47 , 58 , 59 ]. The different position of ndhH in the JSA border suggests that these variations may be caused by intramolecular recombination during early evolution [ 60 , 61 , 62 ].…”
Section: Discussionsupporting
confidence: 91%
“…It is observed that the number of SSRs in the non-coding region was higher than that in the coding region ( Table S5 ). These results are similar to those of other Triticeae species [ 23 , 47 , 48 ] and may be the reason why the mutation rate in IGS regions is higher than in the coding regions [ 49 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The obvious nucleotide bias may be due to the lower number of hydrogen bonds and lower energy consumption of A/T bases (Niu et al, 2017;Kim and Cheon, 2021). Previous studies have reported a higher A/T than G/C content in most plants, which may be due to the large number of A/T-type SSRs (Wang et al, 2021;Wu et al, 2021;Han et al, 2022). In this study, we analyzed the number, location, and composition of SSRs in the cp genomes of five Artemisia species and provided a new reference for further research on molecular markers, mutation hotspots, population genetics, and crop breeding.…”
Section: Figurementioning
confidence: 99%
“…Therefore, the plastome is a useful tool to improve the certainty of phylogenetic trees [ 27 , 28 ]. The plastome generally is 115 to 165 kb in length, containing a large single-copy region (LSC), two separately inverted repeat regions (IRs), and one small single-copy region (SSC), and encodes about 110–130 unique genes [ 29 31 ]. Comparative analysis of plastomes reveals the variation in its structural combination and gene arrangement, which is helpful to further identify the mutational hotspots for species authentication [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%